Green synthesis, characterization and antioxidant potential of silver nanoparticles biosynthesized from de-oiled biomass of thermotolerant oleaginous microalgae Acutodesmus dimorphus. Issue 76 (29th July 2016) - Chokshi, Kaumeel; Pancha, Imran; Ghosh, Tonmoy; Paliwal, Chetan; Maurya, Rahulkumar; Ghosh, Arup; Mishra, Sandhya
Abstract : Antioxidant activity of silver nanoparticles biosynthesized from de-oiled biomass of microalgae A. dimorphus . Abstract : Metal nanoparticles have received global attention due to their widespread biomedical applications. This study demonstrates a sustainable approach for the biogenic synthesis of silver nanoparticles using lipid extracted residual biomass of microalgae Acutodesmus dimorphus cultivated in dairy wastewater. A. dimorphus is a thermotolerant green microalgae with biofuel production potential. The residual biomass of A. dimorphus left after lipid extraction was used to prepare microalgal water extract which was further used for the synthesis of silver nanoparticles. Characterization of the biosynthesized silver nanoparticles using ultraviolet-visible spectrophotometry, Fourier transform infrared spectroscopy, atomic force microscopy, scanning electron microscopy, transmission electron microscopy and energy-dispersive X-ray spectroscopy confirmed the formation of polydispersed, spherical shaped silver nanoparticles with 2–20 nm size. To our best knowledge, this is the first report on the biosynthesis of nanoparticles using de-oiled biomass of microalgae. Further, the biosynthesized silver nanoparticles exhibited an antioxidant potential which was evaluated using 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) i.e. ABTS and 1, 1-diphenyl-2-picrylhydrazyl i.e. DPPH, free radical scavenging assays. As microalgae are widely distributed in diverse habitats, they exhibit wide potential for the green synthesis of metallic nanoparticles. Such integration of phycology and nanotechnology leads to the development of a new interdisciplinary approach, 'phyconanotechnology'.